Sucker pruning management to change the harvest date in banana - Domingues Lima, Juliana; Lelles Moreira Begueline, Maria Clara; Rozane, Danilo Eduardo; Nardini Gomes, Eduardo; Modenese Gorla da Silva, Silvia Helena; de Souza Sales, Victor Ulgo (Comunicata Scientiae, 2021)
In banana crop, sometimes it is necessary to manage seasonal production variations. The aim of the present study was to evaluate the effect of the selection of late successor sucker on the productive unit, compared to the selection of early successor sucker on the growth, harvest date and bunch mass of 'Prata' and 'Nanica' banana. The experimental design was completely randomized, with two treatments and ten replicates, considering two experiments, one for each cultivar. Treatments were conventional pruning (selection of early successor sucker) and modified pruning (selection of late successor sucker), which were established in September, with the destruction of the apical meristem of the successor sucker in modified pruning. The growth of the first and second suckers was quantified at intervals of about 60 days until the reproductive stage and bunch mass was determined. For both cultivars, pruning reduced the height and perimeter of the first successor sucker pseudostem and delayed the harvest date for at least 30 days, without reducing bunch mass. Regardless of sucker pruning management, production averages were 26.68 and 50.64 ton ha-1, respectively, for 'Prata' and 'Nanica' cultivars. For the second sucker, there was residual effect of pruning on the height of 'Nanica' cultivar, but not on production. Establishing the modified pruning is feasible for change harvest date of two cultivars, without increasing costs.